Biomarker analysis for patients with pancreatic cancer treated with nanoliposomal irinotecan plus 5-fluorouracil/leucovorin - Takeshi Kawakami; Akiko Todaka; Kotoe Oshima; Kunihiro Fushiki; Satoshi Hamauchi; Takahiro Tsushima; Tomoya Yokota; Yusuke Onozawa; Hirofumi Yasui; Kentaro Yamazaki (BMC Cancer, 2023)
Abstract Background Nanoliposomal irinotecan plus fluorouracil/leucovorin (5-FU/LV) is a standard second-line therapy for patients with pancreatic cancer. Identification of biomarkers is important to determine appropriate treatment strategies. We investigated the clinical practice outcomes and biomarkers associated with the nanoliposomal irinotecan plus 5-FU/LV regimen. Methods We retrospectively reviewed the data of patients treated with nanoliposomal irinotecan plus 5-FU/LV as a second or subsequent treatment after gemcitabine-based therapy between June 2020 and March 2021 at Shizuoka Cancer Center. Results We analyzed 55 consecutive patients who met the selection criteria. At a median of 9.4 months, median progression-free survival (PFS) and median overall survival (OS) were 2.3 and 6.6 months, respectively. Multivariate analysis showed that Glasgow prognostic score (GPS) was significantly associated with PFS (hazard ratio [HR] 2.16; 95% confidence interval [CI] 1.09–4.30; P = 0.028) and OS (0 vs. 1 or 2: HR 2.46; 95% CI 1.15–5.25; P = 0.029). The OS was significantly longer in patients with CA19–9 response than in those without CA19–9 response (12.6 vs. 5.6 months; HR 0.24; 95% CI 0.08–0.75; P = 0.014). Conclusions Nanoliposomal irinotecan was efficacious and tolerable in clinical practice. GPS and CA19–9 response were good candidates as predictive biomarkers, whereas GPS was a good candidate prognostic biomarker for the nanoliposomal irinotecan plus 5-FU/LV regimen.